Association of torque teno virus viremia with liver fibrosis in the first year after liver transplantation - Engel, Bastian; Görzer, Irene; Campos-Murguia, Alejandro; Hartleben, Björn; Puchhammer-Stöckl, Elisabeth; Jaeckel, Elmar; Taubert, Richard (Frontiers in Immunology, 2023)
Introduction Torque teno virus (TTV) replication is controlled by immune status, mirroring a degree of immunosuppression after solid organ transplantation. TTV viraemia (TTVv) was associated with acute cellular rejection and infection within the first year after liver transplantation (LT). Long-term data on TTV after LT and correlation with graft injury from protocol biopsies are limited. Methods One hundred plasma samples paired with graft biopsies from a prospective single-center biorepository were analyzed. Results The median time post-LT was 23 months (range, 2–298). TTVv was detectable in 97%. TTVv decreased over time after LT and showed a significant decline from year 1 to later time points. Hence, TTVv correlated negatively with histologic liver fibrosis (liver allograft fibrosis and Ishak scores) and positively with the overall immunosuppression degree quantified by an immunosuppression score in the first year after LT. There was no association with dosages or trough levels of single immunosuppressants. The pharmacodynamic marker TTVv did not correlate with pharmacokinetic assessments of immunosuppression degree [calcineurin inhibitor (CNI) trough levels or immunosuppressant dosages]—our clinical gold standards to guide immunosuppressive therapy. TTVv was independently associated with histologically proven liver fibrosis after LT in the first year after LT in multivariate analysis Discussion The independent association of histological graft fibrosis with lower TTVv in year 1 underscores that a pharmacodynamic marker would be preferable to individualize immunosuppression after LT. However, a high variability of TTVv at the low immunosuppression doses given after the first year precludes TTV as a clinically useful marker after LT in the long-term liver transplant recipients.